The oldest fungus gnat of the tribe Exechiini in the lowermost Eocene Oise amber (Diptera: Mycetophilidae) - Camier, Marie; Nel, Andre (Zootaxa, 2020)
Eoexechia gallica gen. n. and sp. n., oldest record of the fungus gnat tribe Exechiini, is described from the Lowermost Eocene amber of France. It falls as sister group of all the extant Exechiini after its addition to the morphological phylogenetic analysis of the tribe. Its discovery suggests a Paleocene age for the Exechiini, in accordance with the current phylogenetic dating. This new discovery will help to date the whole clade in future phylogenies.